Phylogenomic assessment of drug-resistant Mycobacterium tuberculosis strains from Beira, Mozambique. (March 2020) - Namburete, Evangelina Inacio; Dippenaar, Anzaan; Conceição, Emilyn Costa; Feliciano, Cinara; Nascimento, Margarida Maria Passeri do; Peronni, Kamila Chagas; Silva, Wilson Araújo; Ferro, Josefo João; Harrison, Lee H.; Warren, Robin Mark; Bollela, Valdes Roberto
Abstract: Background: Mozambique is a high-burden tuberculosis (TB) country where TB/HIV co-infection and drug resistant TB (DR-TB) incidence is increasing. Whole genome sequencing (WGS) comprehensively describes the molecular epidemiology of TB, allows prediction of DR-TB phenotypes, lineages strains identification and better understanding of transmission chains. Objective: To describe genetic diversity of DR-TB Mycobacterium tuberculosis isolated in Beira, Mozambique. Methods: Descriptive cross-sectional study with 35 M. tuberculosis isolates, resistant to at least one first-line drug on molecular drug-susceptibility tests (DST). Variant identification, DR prediction and phylogenetic analysis provided by WGS, drug-susceptibility pattern compared to line-probe assay (LPA): Genotype MTBDR TM plus and MTBDR TM sl . Findings: Lineage 4 (L4) was the most prevalent: 25 (71.4%) isolates; 5 (14.3%) L1 and 5 (14.3%) L2. WGS showed 33/35 (94.3%) isolates resistant to at least one drug, two pan-susceptible isolates that were previously diagnosed as DR-TB with genotype MTBDR plus . Concordance between WGS and LPA: 88.6% for isoniazid (INH), 85.7% to rifampicin (RPM), 91.4% for quinolones and 100% to second line injectable drugs. There were three possible TB transmission chains, 10 strains showing recent transmission. Conclusion: WGS provided reliable information about the most frequent lineages related to DR-TB in Beira, Mozambique: L4.3 (LAM), L2 (Beijing) and L1 (EAI) and possible recent transmission chain.